Government Debt as Insurance against Macroeconomic Risk - Martin Barbie; Marcus Hagedorn; Ashok Kaul (Institute for the Study of Labor (IZA), 2001)
Is there a role for debt beyond curing overaccumulation of capital? Does dynamic efficiency and the infeasibility of debt Ponzi schemes eliminate any Pareto-improving role for a government in a competitive economy with complete markets? Is there an optimal maturity structure of public debt? Using a stochastic Diamond OLG model, we tackle these questions. We show that government debt can Pareto-improve upon market allocations through a mechanism that resembles a Ponzi scheme. But instead of rolling over safe debt, we can interpret our scheme as one that rolls over an insurance contract generation for generation. This kind of dynamic risk-sharing can provide insurance against macroeconomic risk. Using the widespread welfare concept of interim Pareto optimality, we ensure that all generations voluntarily participate in our insurance scheme. Yet, the scheme cannot be replicated on capital markets. Exploiting information from the term structure of interest rates, we derive testable conditions both for dynamic efficiency and for interim Pareto optimality in terms of interest rates. We provide evidence that real world economies, while being dynamically efficient, are likely not to be interim Pareto optimal. We conclude that there may be a welfareimproving role for a well-designed maturity structure of debt.
Keywords: H63; H55; E43; D61; 330; Stochastic OLG model; government debt; macroeconomic risk; dynamic efficiency; interim pareto optimality; maturity structure; Öffentliche Schulden; Finanzpolitik; Overlapping Generations; Makroökonomischer Einfluß; Schock; Pareto-Optimum; Debt Management; Laufzeit; Theorie